National Commission for Scheduled Castes and Scheduled Tribes Fourth Report 1996-97 and 1997-98 Volume I - Planning Commission (Planning Commission, 1996)
The State Governments have to ensure that funds allotted under SCP and TSP are at least in proportion to the percentage of their population as per the Planning Commission guidelines and the schemes that are devised are truly helpful to the SC/ST families. It is to be further ensured that there should be no diversion of funds from the SCP and TSP kitty and the utilisation of the Special Central Assistance and grants from Government of India are made for full benefit of the SCs and STs.
Fourth Report 1996-97 and 1997-98
National Commission for Scheduled Castes and Scheduled Tribes